QARAQALPAQ MILLIY SAZ ÁSBAPLARINIŃ RAWAJLANIW TARIYXI - Esanov, M. (SCIENCE and SOCIETY, 2023)
The national music of the Karakalpaks is one of the most famous of the chants, which is transmitted by word of mouth, from generation to generation, from teacher to student. Teaching national music to students in schools develops patriotism for the Fatherland.